Groundwater Quality Characterization for Safe Drinking Water Supply in Sheikhpura District of Bihar, India: A Geospatial Approach - Kumar, Ritesh; Singh, Sarnam; Kumar, Rakesh; Sharma, Prabhakar (Frontiers in Water, 2022)
Groundwater quality due to geogenic factors, aggravated by anthropogenic activities, is a significant threat to human wellbeing and agricultural practices. This study aimed at mapping the spatial distribution of low and high groundwater-contaminated regions in the Sheikhpura district of Bihar for safe drinking and irrigation water availability. To account for spatial distribution, groundwater quality parameters, such as fluoride, iron, total dissolved solids, turbidity, and pH, were analyzed using integrated interpolation, geographical information systems, and regression analysis. A total of 206 dug wells and bore wells were analyzed for in-situ observations in the Sheikhpura district of Bihar, India. The analysis indicated that the periphery south of Chewara and Ariari blocks, i.e., about 9.16% of district area, is affected by fluoride content (1.55–2.32 mg/l) which is highly unsuitable for consumption, as recommended by the WHO and BIS standards. However, the remaining area (90.84%) is within the permissible limit of fluoride content (0.37–1.54 mg/l). In most areas, iron content is beyond WHO permissible limits (>0.1 mg/l), except 3.1% area in the eastern region with 0.06–0.12 mg/l iron, although iron concentrations in groundwater are under the acceptable limit (<0.3 mg/l) as per BIS standard across the district. However, pH and total dissolved solids were within permissible limits. Each of the modeled geospatial maps was validated using a set of 17 in-situ observations. The best-fit model between observed and predicted variables such as fluoride, iron, total dissolved solids, and pH produced a coefficient of determination (R2) of 0.96, 0.905, 0.91, and 0.906, respectively. The findings of this study provide insights and understanding on groundwater pollution regimes and minimize uncertain causes because of the high spatial distribution of geogenic fluoride and iron occurrence, and will also be helpful to policymakers for better planning, investments, and management to supply potable water in the area.